Highly dynamic mechanical transitions in embryonic cell populations during Drosophila gastrulation - Juan Manuel Gomez; Carlo Bevilacqua; Abhisha Thayambath; Jean-Karim Heriche; Maria Leptin; Julio M. Belmonte; Robert Prevedel (Nature Communications)
Abstract During development, three-dimensional morphology arises from the balance of forces acting on cells and tissues, and their material properties. Cellular forces have been investigated, however the characterisation and specification of cell material properties remains poorly understood. Here, we characterise and spatially map in three dimensions the dynamics of the longitudinal modulus at GHz frequencies to characterise the evolving blastoderm material properties during Drosophila gastrulation utilising line-scan Brillouin microscopy. We find that blastoderm cells undergo rapid and spatially varying changes in their material properties and that these differ in cells with different fates and behaviours. We identify microtubules as potential mechano-effectors, and develop a physical model to understand the role of localised and dynamic changes in material properties during tissue folding. Our work provides the first spatio-temporal description of evolving material properties during organismal morphogenesis, and highlights the potential of Brillouin microscopy for studying the dynamic changes in cell shape and cell material properties simultaneously.